Variações sobre uma Arqueologia da Atualização - Schwäbl, Tiago (MATLIT: Materialities of Literature, 2016)
Review of Siegfried Zielinski, [… After the Media] News from the Slow-fading Twentieth Century. Minneapolis, Minnesota: Univocal, 2013. 276 pp. ISBN 9781937561161. DOI: http://dx.doi.org/10.14195/2182-8830_4-1_16